Crash in the Jungle - Alderson, Jim (Stanley Thornes Publishers Ltd, 1990)
Suddenly the plane was thrown about all over the place. Bags and cases fell off the racks. Men and women began to scream$1! =s
Keywords: Juvenile Fiction / Adventure